Damages and Injuries made by His Majesty Soldiers. Wintering of the Polish Army by 1564/1565 - Bołdyrew, Aleksander (Armia kontra natura, 2020)
Distanced theatres of operations during the First Northern War (1560–1570) forced a necessity of keeping some armed forces on alert even at winter. Since lack of regular military salaries’ withdrawals and the centralised system of providing to the army, the overwintering soldiers had to supply the eatables and the forage themselves, what lead to numerous malpractices. In the summer of 1565 the special mixed Polish-Lithuanian committee which formed. Its task was to inventory and to pay for the damages caused by Polish soldiers while winter quarters (1564/1565). The records of the committee are an interesting account of troopers’ struggle with the winter, lack of the aliment and the convenient conditions.